Literature Review: Ethnomathematics of the Angkola Batak Tribe in Mathematics Learning - Nurhasanah Siregar; Syawal Gultom; Mangaratua M Simanjorang (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This research is to find out whether ethnomathematics in the Angkola Batak culture can be used in mathematics learning, and it seeks to know which cultural artifact or philosophy of ethnomathematics is more widely used in learning. Method: This research is a literature review by collecting metadata through the PRISMA model. Articles from Google Scholar from 2018 to 2023 were collected with the help of Publish and Perish. This methodology consists of well-defined review stages, eligibility criteria developed and explained from information sources, a literature search strategy, a literature selection process, and data synthesis based on the literature. Results: Of the 14 articles used as research samples, there were four articles each for elementary school (ES) and junior high school (JHS), meaning ethnomathematics is more suitable for use at elementary and middle school levels. Using cultural artifacts as a learning medium is more common than using philosophy from that culture. Novelty: This research produces information that learning using ethnomathematics is more suitable for children with a semi-concrete learning level.